Efficacy and Safety of Novel Beta-Chitin Patches as Haemostat in Rat Vascular and Neurosurgical Model - Sabab, Ahad; Vediappan, Rajan Sundaresan; Finnie, John; McAdam, C. John; Jukes, Alistair; Vreugde, Sarah; Wormald, Peter-John (Frontiers in Surgery, 2022)
Background: Intraoperative haemorrhage is a major cause of poor post-operative outcome. Beta-chitin patch has previously been found to be an effective haemostat, but whether modifying the patch can improve its efficacy and safety, remains unknown. In this study, beta-chitin patches were modified using polyethylene oxide, Pluronic-F127 (Chi/F127), calcium (Chi/20%Ca), increased thickness (Chi/Thick) or polyphosphate (Chi/PP). Objective: Using rat (Wistar Albino; 8-10 weeks old) vascular and neurosurgical models, this project investigated and compared the efficacy and safety of beta-chitin patches with gauze, Surgicel and FloSeal. Methods: Ninety rats underwent a standardized femoral artery injury and were randomized to receive either beta-chitin patches, gauze, Surgicel or FloSeal. The bleeding time and total blood loss was measured. For the neurosurgical model, forty-four rats underwent a standardised cortical injury and randomization to a treatment group. Following a 48hr recovery period, their brains were collected for histopathological examination. Results: The mean bleeding time with Chitin (120.8s) and Chi/PP (117.3s) was approximately 60s lower than Chi/F127, Chi/20%Ca and Chi/Thick (p<0.05). Chitin and Chi/PP had a significantly lower bleeding time than FloSeal (174.2s) (p<0.05), but not Surgicel (172.7s). Gauze (400s) had a significantly higher bleeding time compared to all other groups (p<0.05). There were no significant differences in the total blood loss between the groups. Histopathological examination of brains found no adverse inflammatory reaction to any of the haemostatic compounds. Conclusion: Chi/PP had superior haemostatic efficacy compared to Surgicel and FloSeal, but not compared to non-modified beta-chitin patch. All of the haemostats were equally safe.